Penerapan Self Organizing Map (SOM) dan Radial Basis Function (RBF) Untuk Memprediksi Kecepatan Angin Di Perairan Kota Tanjungpinang - Julia, Rini Hervianti; Nikentari, Nerfita; Hayaty, Nurul (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2018)
Wind is very important role in human life, one of them for fishermen, natural conditions play an important role in the fluency of their activities, especially for the people of Tanjungpinang who lived in coastal areas as fishermen. But it will be a problem if the winds move with high intensity that will impact bad weather. To be able to monitor the movement of wind speed, this study made predictions using the method Self Organizing Maps (SOM) and Radial Basis Function (RBF) to predict wind speed. In this study the data used for daily wind speed prediction starts from January 2014 - October 2017. The results of the tests conducted with the 418 of data, the number of clusters obtained 33 from the training process produce 1,51 of RMSE and 28.98% of MAPE and 71,02% of accuracy.